Oral lesions diagnosed by biopsy in the municipality of Palmas, Tocantins, Brazil: a 12-year retrospective study (Research, Society and Development, 2022)
The oral cavity is often affected by a range of lesions, which can range from malignant to benign. In this context, biopsies are essential tools for establishing diagnoses. Histopathological results are generally influenced by clinical data and demographic determinants; thus, knowledge of location, age, ethnicity, and sex are useful in determining the predilections of different types of disease in each individual. From the epidemiological survey of oral lesions (OL), it is possible to assess their distribution in the population studied, thus identifying risk groups and optimizing the allocation of health services. Based on the lack of epidemiological studies that assess the prevalence of oral cavity lesions in Tocantins, this study aimed to identify the prevalence and distribution of oral lesions diagnosed through biopsy in the Stomatology service of the Centro de Especialidades Odontológicas de Palmas (CEO). This is a descriptive, retrospective cross-sectional study in which 854 biopsy records were analyzed over a period of 12 years. Among the most diagnosed OLs are the Reactive/Inflammatory Lesions LRI (31%), possibly due to the greater number of patients using prostheses seen at the service; then, the most prevalent were the Salivary Gland Lesions LGS (19%) and the Benign Neoplasms NB (18%). Finally, 9.8% of the OL found were grouped as malignant and pre-malignant disorders, emphasizing the importance of prevention regarding predisposing factors. There is a need for more scientific research aimed at OL in the state of Tocantins, so that there are prevention programs aimed at combating the most frequent conditions.